Eskalasi Bahasa Indoglish Dalam Ruang Publik Media Sosial - Wahyu Oktavia (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2019)
Indoglish is a unique and unique form of language and is a blend of English and Indonesian. The purpose of this study is to describe the phenomenon of indoglish language escalation in the public space of social media. The form of this study is descriptive qualitative which as a whole utilizes the methods of interpretation by presenting it in the form of descriptions of words. Research data comes from various written languages ​​obtained from facebook, whatsapp and instagram.. Data collection is used the method of note and note. Data analysis techniques are carried out through data reduction, data presentation and verification. The results of the study show that there are a) form of indoglish language, b) classification of indoglish languages ​​based on Indonesian elements in foreign languages ​​and foreign elements in Indonesian, c) factors that cause indoglish language namely age, linguistic, historical, foreign language influences, word needs new, equivalent Foreign or non-standard words, and social and cultural.